Influence of barium substitution on bioactivity, thermal and physico-mechanical properties of bioactive glass - Arepalli S.K.; Tripathi H.; Vyas V.K.; Jain S.; Suman S.K.; Pyare R.; Singh S.P. (My University, 2025)
Barium with low concentration in the glasses acts as a muscle stimulant and is found in human teeth. We have made a primary study by substituting barium in the bioactive glass. The chemical composition containing (46.1 - X) SiO2 --24.3 Na2O-26.9 CaO-2.6 P2O5, where X = 0, 0.4, 0.8, 1.2 and 1.6 mol% of BaO was chosen and melted in an electric furnace at 1400 ± 5 °C. The glasses were characterized to determine their use in biomedical applications. The nucleation and crystallization regimes were determined by DTA and the controlled crystallization was carried out by suitable heat treatment. The crystalline phase formed was identified by using XRD technique. Bioactivity of these glasses was assessed by immersion in simulated body fluid (SBF) for various time periods. The formation of hydroxy carbonate apatite (HCA) layer was identified by FTIR spectrometry, scanning electron microscope (SEM) and XRD which showed the presence of HCA as the main phase in all tested bioactive glass samples. Flexural strength and densities of bioactive glasses have been measured and found to increase with increasing the barium content. The human blood compatibility of the samples was evaluated and found to be pertinent. © 2015 Elsevier B.V.